The Analysis of Absolute Convergency of Human Development Inter Provinces in Indonesia - Ana Syukriyah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2016)
The purpose of this study was to identify the sigma and absolute beta convergence of the Human Development Index (HDI) inter provinces in Indonesia, and identify the speed of absolute beta convergence. This study used a quantitative analysis with tool used is regression panel data with fixed effect model Generalize Least Square method (GLS). The results shows that there happen sigma convergence of HDI and absolute beta convergence of HDI inter provinces in Indonesia. The speed of absolute convergence is equal to 0.807 percent annually.